Pompey's Head and Caesar's Tears: the History of an Anecdote - Vassiliades, Georgios (Classica et Mediaevalia, 2022)
In many sources, Caesar is said to have wept and become indignant at the sight of Pompey’s head presented to him as a gift from Ptolemy XIII. Given that Caesar does not mention the episode in De Bello Ciuili, this paper attempts, through a chronological survey of later extant sources, to determine their interdependence by observing the stable and fluid elements in each, and then to outline the history of the shaping of this anecdote. The episode might have been included in early accounts of the events surrounding Pompey’s death, produced by pro-Caesarian historians in the immediate aftermath of Caesar’s death. Declamatio not only picked up and reworked this historical anecdote and led to its reinterpretation in an anti-Caesarian way, but also probably played a major role in its broader diffusion.